Pengaruh Metode Outdoor Learning terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV di MIS YPI Batang Kuis - M. Kholidtur Rahman Lubis; Tri Indah Kusumawati; Aufa Aufa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The research that has been conducted is entitled "The Effect of the Outdoor Learning Method on the Ability to Write Descriptive Writing of Class IV Students at MIS YPI Batang Kuis" and is based on the phenomenon that the ability to write is still very limited, especially writing descriptive essays. In this case, it can result in student creativity not being able to develop optimally and find it difficult to find new ideas or ideas in the learning process. The research methodology used quantitative research quasi experiment design. The population in this study were all grade IV students of MIS YPI Batang Kuis consisting of IV A and IV B totalling 47 students. The sampling technique was carried out by Non Probability Sampling, through the form of total sampling (Boring Sampling). That is, choosing a sample with all the population being sampled and the population can only be two classes. This research instrument is in the form of a description essay writing test and documentation. Data processing tools use data requirement tests and t tests. The results of the study revealed that (1) the average pre-test of the experimental class was 65.09 while the average pretest of the control class was 64.21, (2) the average posttest of the experimental class after being given treatment in the form of learning using outdoor learning methods was obtained at 83.12 while the average posttest of the control class was given treatment in the form of conventional learning obtained an average of 72.54 Thus it can be concluded that the average posttest of the experimental class is higher than the average posttest of the control class. (3) The results of the t test calculation obtained tcount greater than ttable (2.915> 2.074), so it can be concluded that Ha is accepted and Ho is rejected. Based on the research findings above, it follows that the use of outdoor learning methods in the learning process has an effect on the ability to write descriptive essays in class IV YPI Batang Kuis School Year 2023/2024.